Craniomegaly in Neonate and Infants Requiring Neurosurgical Intervention: An Experience at Tertiary Care Center - Sangh Mittra; Hanuman Prasad Prajapati; Raj Kumar (Indian Journal of Neurosurgery)
Background The identification of neurosurgical causes of craniomegaly and early institution of therapy requires for better clinical and functional outcomes. Aims and Objectives The aim of this study was to evaluate the neurosurgical causes, managements, and outcomes of craniomegaly in neonate and infants. Materials and Methods The cases with a history of head enlargement from neonatal period were included in this study. Their causes, managements, and outcomes were recorded retrospectively during the period of January 2010 to February 2013, in neurosurgery department at SGPGIMS Lucknow, and June 2018 to June 2020, at UPUMS, Saifai, Etawah, UP, India. Results Out of 41 cases, there were 30 (73.14%) cases of hydrocephalus, 4 (9.76%) Dandy-Walker malformation, 2 (4.88%) subdural collection, 2 (4.88%) arachnoid cyst, 1 (2.44%) craniosynostosis, and 2 (4.88%) with tubercular meningitis. The age range of our cases was 18 to 178 days and the mean age was 102.54 ± 50.73. Preoperative head circumference range was 39 to 62 cm (mean: 55.27 ± 6.58cm). Majority of the cases (n = 32, 78.05%) were managed with ventriculoperitoneal shunt surgeries. Out of 41 cases, 33(80.49%) had improved outcomes, 7 (17.07%) stabilized, and mortality occurred in 1 (2.44%) case. Postoperatively, there was improvement in the head circumference (range: 39–60 cm and mean: 46.15 ± 5.83 cm) on 6 to 24 months (mean: 17.85 ± 5.18 months) of follow-up. Conclusion Hydrocephalus was the commonest neurosurgical cause of head enlargement in neonate and infants. Shunt surgery was the most common form of management of these cases. Early detection, institution of therapy, and periodic follow-up program for diagnosing and treating complications were the key to successful outcomes in these patients.